Paleo-Ecology of the Yedoma Ice Complex on Sobo-Sise Island (EasternLena Delta, Siberian Arctic) - Wetterich, S.; Rudaya, N.; Nazarova, L.; Syrykh, L.; Pavlova, M.; Palagushkina, O.; Kizyakov, A.; Wolter, J.; Kuznetsova, T.; Aksenov, A.; Stoof-Leichsenring, K. R.; Schirrmeister, L.; et al. (Frontiers in Earth Science, 2021)
Late Pleistocene permafrost of the Yedoma type constitutes a valuable paleo-environmental archive due to the presence of numerous and well-preserved floral and faunal fossils. The study of the fossil Yedoma inventory allows for qualitative and quantitative reconstructions of past ecosystem and climate conditions and variations over time. Here, we present the results of combined paleo-proxy studies including pollen, chironomid, diatom and mammal fossil analyses from a prominent Yedoma cliff on Sobo-Sise Island in the eastern Lena Delta, NE Siberia to complement previous and ongoing paleo-ecological research in western Beringia. The Yedoma Ice Complex (IC) cliff on Sobo-Sise Island (up to 28 m high, 1.7 km long) was continuously sampled at 0.5 m resolution. The entire sequence covers the last about 52 cal kyr BP, but is not continuous as it shows substantial hiatuses at 36–29 cal kyr BP, at 20–17 cal kyr BP and at 15–7 cal kyr BP. The Marine Isotope Stage (MIS) 3 Yedoma IC (52–28 cal kyr BP) pollen spectra show typical features of tundra–steppe vegetation. Green algae remains indicate freshwater conditions. The chironomid assemblages vary considerably in abundance and diversity. Chironomid-based TJuly reconstructions during MIS 3 reveal warmer-than-today TJuly at about 51 cal kyr BP,46-44 and 41 cal kyr BP. The MIS 2 Yedoma IC (28–15 cal kyr BP) pollen spectra represent tundra-steppe vegetation as during MIS 3, but higher abundance of Artemisia and lower abundances of algae remains indicate drier summer conditions. The chironomid records are poor. The MIS 1 (7–0 cal kyr BP) pollen spectra indicate shrub-tundra vegetation. The chironomid fauna is sparse and not diverse. The chironomid-based TJuly reconstruction supports similar-as-today temperatures at 6.4–4.4 cal kyr BP. Diatoms were recorded only after about 6.4 cal kyr BP. The Sobo-Sise Yedoma record preserves traces of the West Beringian tundra-steppe that maintained the Mammoth fauna including rare evidence for woolly rhinoceros’ presence. Chironomid-based TJuly reconstructions complement previous plant-macrofossil based TJuly of regional MIS 3 records. Our study from the eastern Lena Delta fits into and extends previous paleo-ecological Yedoma studies to characterize Beringian paleo-environments in the Laptev Sea coastal region.